Recursos didácticos en el Área de Ciencias Naturales y su influencia en el aprendizaje de los Estudiantes del Octavo Grado de Educación General Básica de la Unidad Educativa La Maná, durante el período escolar 2016-2017 - Espín León, Edison Fabián (2017)
In the project it was determined the influence of didactic resources in the learning of the students of the eighth grade of basic general education of the Educational Unit “La Maná”, morning section during the academic period 2016-2017 in the area of science concluding with the application of didactic alternatives that allowed to improve the teaching process of the students returning to the significant and interesting program contents that facilitated to construct dynamic and practical learning with the use of materials that were elaborated with objects recyclable elements awakening in the students the interest and the creativity. The investigation was based fundamentally on the need to understand that the area of science is eminently experimental taking into consideration that the acquisition of learning is based on the discovery and approval for it is pertinent to have didactic resources that allow to make learning to verify and not only to know from there arose the objectives that made it possible to diagnose the influence of the didactic resource in the learning of this area. The obtained information allowed to elaborate a didactic guide for the design and elaboration of didactic resources that at the same time to improve process of learning in the natural sciences and to make of it on entertaining dynamic area and experimental allowed to use recyclable objects to reduce the pollution and to strengthen the care of the environment offered also the possibility that the teachers, students and parents have didactic alternatives that improve the acquisition of knowledge.